Barriers to digital transformation in a South African water utility - Paima, Veshal (University of the Witwatersrand, Johannesburg, 2023)
This study offers a qualitative examination of the barriers hindering a leading South African water utility, referred to here as Organisation X, from fully embracing digital transformation. The qualitative case study scrutinises the utility's attempts at digitalising its processes for better efficiency and the significant barriers that disrupt the realisation of its digital initiatives. Through interviews, this study captures the perspective of these challenges from individuals deeply engaged in the digital transformation journey. The findings shed light on the intricate barriers that Organisation X faces, encompassing organisational culture, the integration of new digital tools with existing systems, governance, leadership, impacts on the value chain, and the overarching capacity for innovation. The conceptual framework of this study delves into the relationship between the organisation's strategy and its business model, focusing on how digital transformation can drive value creation by refining business operations. By investigating these factors, the study seeks to deeply understand the barriers that Organisation X faces in its quest to effectively implement digital strategies and advance its digital maturity. Furthermore, by evaluating the operational strategies of Organisation X, the research pinpoints congruencies, and disparities with its digital ambitions
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business Johannesburg, 2023
Keywords: Culture; Digital Strategy; Digital transformation; Knowledge Management System; Management Information System; Stakeholder management; UCTD; SDG-9: Industry, innovation and infrastructure